Permo-Carboniferous Carbonate Platforms and Reefs
DOI: 10.2110/pec.03.78.0201
|View full text |Cite
|
Sign up to set email alerts
|

Upper Carboniferous-Lower Permian Buildups of The Carnic Alps, Austria-Italy

Abstract: A variety of buildup types occur in the upper Paleozoic Auernig and Rattendorf Groups, Carnic Alps, at the present-day Austrian-Italian border, including coral, diverse algal (Anthracoporella, Archaeolithophyllum, Rectangulina, and phylloid green), bryozoan, brachiopod, and sponge buildups. Thin mounds and banks have a diverse fossil association (e.g., Archaeolithophyllum-bryozoanbrachiopod mounds) and occur in siliciclastic-dominated intervals, as do coral buildups. Some of the biodiverse thin mounds occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…The widespread Anthracoporella and phylloid algal mounds (facies Md3 and Md4), commonly assigned to shallow, low-energy settings (Krainer, 1995;Samankassou, 1997Samankassou, , 1998Samankassou, , 1999Soreghan and Giles, 1999;Samankassou, 2003), the abundance of chaetetid sponges, calcareous green algae and large benthic foraminifers (fusulinoideans, palaeotextulariids, bradyinids and Staffella) along with levels rich in Osagia-type oncoids agree with this interpretation. The various types of buildups in the study area are comparable to those reported throughout Late Palaeozoic deposits by previous authors.…”
Section: Mid-rampmentioning
confidence: 54%
See 1 more Smart Citation
“…The widespread Anthracoporella and phylloid algal mounds (facies Md3 and Md4), commonly assigned to shallow, low-energy settings (Krainer, 1995;Samankassou, 1997Samankassou, , 1998Samankassou, , 1999Soreghan and Giles, 1999;Samankassou, 2003), the abundance of chaetetid sponges, calcareous green algae and large benthic foraminifers (fusulinoideans, palaeotextulariids, bradyinids and Staffella) along with levels rich in Osagia-type oncoids agree with this interpretation. The various types of buildups in the study area are comparable to those reported throughout Late Palaeozoic deposits by previous authors.…”
Section: Mid-rampmentioning
confidence: 54%
“…Anthracoporella-dominated algal mounds, first described in the Carnic Alps by Krainer (1995) and Samankassou (1997Samankassou ( , 1998Samankassou ( , 1999Samankassou ( , 2003, were rarely reported in coeval successions elsewhere. Overall, the studied Anthracoporella mounds show striking similarities to those described in the Carnic Alps.…”
Section: Mid-rampmentioning
confidence: 99%
“…Low-diversity algal mounds occurring throughout Pennsylvanian and Permian deposits strongly support this assumption (Flügel 1979;Toomey 1991;Forsythe et al 2002;Samankassou 2003;Samankassou and West 2003). Indeed, chemical defense used by algae is documented from studies of recent reefs (Hay 1997;Paul 1997) and other environments (G. Gerdes, personal communication, 1998).…”
Section: Biodiversity Ecological Communitymentioning
confidence: 93%
“…Scale bar is 0.5 mm for all Wgures ᭣ Temperature and water depth Phylloid algae in south China, assumedly photosynthetic green algae, are associated with colonial corals and fusulinids: this may point to a shallow-water depositional environment within the photic zone. The growth of phylloid algal reefs is interpreted to have taken place between the lower limit of the photic zone (the deepest) and the zone close to the lower limit of the wave activity (the shallowest) (see Doherty et al 2002;Samankassou 2003). Considering the wide depth ranges of modern green algae and algal mounds (e.g., 20-100 m for Halimeda mounds in the eastern Java Sea; ), a precise water depth cannot realistically be deduced.…”
Section: Biodiversity Ecological Communitymentioning
confidence: 99%
See 1 more Smart Citation